Changing patterns in industrial performance : a UNIDO competitive industrial performance perspective - implications for industrial development - Bartels, Frank L. (UNIDO ViennaAT, 2009)
Views industrial performance through a limited indication of changes in performance across developing and industrialised countries according to income groups and in terms of transactional and transformational dimensions of the economy.